Comprehensive Evaluation of the EDM E-RKAM Program in Madrasah Aliyah Using the CIPP Model - Suzatmiko Wijaya; Candra Wijaya; Abdurrahman Abdurrahman (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study evaluates the implementation of the self-evaluation program for the Madrasah Budget Work Plan (RKAM) based on the electronic Madrasah (e-RKAM) system using the Context, Input, Process, Product (CIPP) evaluation model. Identified challenges include limited human resource competence, suboptimal budget allocation, technical barriers, and variations in the quality of implementation across madrasahs. The study employed qualitative methods—interviews, observations, and documentation—along with percentage techniques to assess each component. The context evaluation revealed that while the program aligns with regulatory requirements and the needs of madrasahs, stakeholder involvement remains uneven, with an average score of 85%. The input evaluation showed delays in work plan development, limited human resources, and poor scheduling, scoring an average of 79%. The process evaluation indicated that the program's implementation is moderately effective but faces obstacles such as limited technological access, resistance to change, and insufficient training, with an average score of 82.75%. The product evaluation demonstrated improvements in data-driven planning and structured budgeting; however, the achievement of performance indicators is still lacking, with an average score of 84.50%. Additionally, the program has not involved the Madrasah Quality Assurance Team. Overall, the program has had a positive impact on madrasah management, though several technical and managerial issues must be addressed to enhance its effectiveness. Recommendations include strengthening technical training, upgrading technological infrastructure, and increasing stakeholder engagement through ongoing monitoring and support.